Recycled concrete aggregate as a base course material in Western Australian road - Jitsangiam, Peerapong; Siripun, K.; Nikraz, H.; Leek, C. (2012)
Recycled crushed concrete and demolition materials have been trailed successfully as a road construction material in a number of locations in Western Australia, but industry acceptance of the material has been minimal. Specifications of such materials currently in use have been modified from commonly used specifications for new quarried products, and remarkably, there have been some doubts about the long term performance and quality control of such recycled products. This paper analyses the performance of recycled concrete pavements that have been constructed in Western Australia, and details the extensive laboratory testing program undertaken to model the product and compare its performance to conventional quarry products. Field testing demonstrates good quality control and performance of recycled crushed concrete and demolition materials superior to conventional quarry products and the laboratory results shows very close characteristics between both materials. © 2012 Taylor & Francis Group.